Fixed-dose combination therapy of nebivolol and valsartan for the treatment of hypertension. (3rd May 2016) - Sander, Gary E.; Fernandez, Camilo; Giles, Thomas D.
ABSTRACT: Recent large clinical trials have refuted earlier suggestions from the Joint National Committee 8 committee that less aggressive targets for blood pressure control were all that could be justified in most hypertensive patients. It now does appear that in fact "lower is better, " with blood pressure targets < 120/80 mm Hg appropriate for many hypertensive patients. Two drug combinations are often indicated as initial therapy if a 20/10 mm Hg or greater blood pressure reduction is necessary to reach target. Combinations consisting of β-blockers and renin-angiotensin-aldosterone system inhibitors have previously been deemed "less effective, " based on partially overlapping mechanisms of action and limited clinical trial evidence. Nebivolol is a vasodilating β1 -selective blocker and β3 - adrenoceptor agonist; β3 -adrenoceptor activation increases nitric oxide concentrations and thus explains the vasodilatory effect. A recent 8-week randomized trial (N=4, 161) in individuals with stage 1-2 hypertension demonstrated that single-pill fixed dose combinations (FDC) of nebivolol and valsartan, an angiotensin II subtype 1 receptor blocker, were more effective in reducing blood pressure than the corresponding monotherapies, with comparable tolerability. In addition, an ABPM-biomarkers substudy from that trial (n=805) demonstrated that the FDC prevented a valsartan-induced increase in plasma renin activity, and that the nebivolol/valsartan 20/320 mg/day dose reduced plasma aldosterone concentration significantly more than valsartan 320 mg/day. This article will describe the properties of nebivolol that make it unique and separate it from other β-blockers, and will further support the pharmacological advantages of this particular combination.